The Effect of Endorsers and Social Media Advertising on Consumer Purchase Decisions of Instagram Social Media Users with Brand Awareness as a Mediating Variable - Edward Yohanes .; Lena Ellitan; C Marliana Junaedi . (Program MM Universitas Surabaya, 2021)
This study aims to examine the effect of endorsers and social media advertising on consumer purchase decisions of Instagram social media users with brand awareness as a mediating variable. The research sample used in this study was 150 samples with a purposive sampling technique. The data used was primary data obtained by distributing questionnaires to Instagram social media users. The data analysis technique used was SEM with Smart PLS 3 software. The results show that social media advertising has a significant effect on brand awareness, endorsers have no effect on brand awareness, brand awareness has a significant effect on consumer purchase decisions, social media advertising has a significant effect on consumer purchase decisions, endorsers have a significant effect on consumer purchase decisions, social media advertising has no effect on consumer purchase decisions through brand awareness, and endorsers have no effect on consumer purchase decisions through brand awareness.